Handedness effects of imagined fine motor movements. Issue 2 (4th March 2018) - Donoff, Christopher M.; Madan, Christopher R.; Singhal, Anthony
ABSTRACT: Previous studies of movement imagery have found inter-individual differences in the ability to imagine whole-body movements. The majority of these studies have used subjective scales to measure imagery ability, which may be confounded by other factors related to effort. Madan and Singhal [2013. Introducing TAMI: An objective test of ability in movement imagery. Journal of Motor Behavior, 45 (2), 153–166. doi:10.1080/00222895.2013.763764 ] developed the Test of Ability in Movement Imagery (TAMI) to address these confounds by using a multiple-choice format with objectively correct responses. Here we developed a novel movement imagery questionnaire targeted at assessing movement imagery of fine-motor hand movements. This questionnaire included two subscales: Functionally-involved Movement (i.e., tool-related) and Isolated Movement (i.e., hand-only). Hand-dominance effects were observed, such that right-handed participants were significantly better at responding to right-hand questions compared to left-hand questions for both imagery types. A stronger handedness effect was observed for Functionally-involved Movement imagery, and it did not correlate with the Edinburgh Handedness Inventory. We propose that the Functionally-involved Movement imagery subscale provides an objective hand imagery test that induces egocentric spatial processing and a greater involvement of memory processes, potentially providing a better skill-based measure of handedness.